Proceedings of the Fifth International Workshop on Knowledge Discovery From Sensor Data 2011
DOI: 10.1145/2003653.2003660
|View full text |Cite
|
Sign up to set email alerts
|

Identifying user traits by mining smart phone accelerometer data

Abstract: Smart phones are quite sophisticated and increasingly incorporate diverse and powerful sensors. One such sensor is the tri-axial accelerometer, which measures acceleration in all three spatial dimensions. The accelerometer was initially included for screen rotation and advanced game play, but can support other applications. In prior work we showed how the accelerometer could be used to identify and/or authenticate a smart phone user [11]. In this paper we extend that prior work to identify user traits such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
(37 reference statements)
0
20
0
1
Order By: Relevance
“…Gait related studies [12, 45, 17] have shown that there are gender differences in human gait; females walk with lesser step width and more pelvic movement, while males move their shoulders more often. In our current experiments, in light of the gender imbalance among our participants, we were unable to articulate this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Gait related studies [12, 45, 17] have shown that there are gender differences in human gait; females walk with lesser step width and more pelvic movement, while males move their shoulders more often. In our current experiments, in light of the gender imbalance among our participants, we were unable to articulate this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Gait information captured by the smartphone's built-in or wearable sensors can decode plenty of useful information about human traits. Weiss et al [10] collected the accelerometer data of 70 participants for sex, height, and weight prediction tasks using conventional feature-based approaches. Sex prediction involved classifying a smartphone user as either male or female, while the height and weight prediction tasks included predicting the user's height in inches and his/her weight in pounds.…”
Section: Inferring Simple Human Traits From Gaitsmentioning
confidence: 99%
“…Data from motion sensors are also multi-dimensional with a special temporal-spatial structure for conventional feature-based approaches [10,11]. Furthermore, the design of a specific feature extractor that transforms raw data into feature vectors relies on heuristic hand-crafted feature engineering and considerable domain expertise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwapisz et al show how collected accelerometer data can be used to uniquely identify the user [24]. Weiss et al [33] show how the same source of information can even be used to identify user traits such as sex, height, and weight of the user. Similar results can be found in [8], [28], [11], [30], and [19].…”
Section: Related Workmentioning
confidence: 99%